Estresse oxidativo, inflamação e hiperparatireoidismo secundário em indivíduos submetidos a terapia renal substitutiva - Renner, Luciana de Oliveira (2023)
Chronic kidney disease (CKD) is characterized by the progressive loss of nephron function, resulting in the loss of the ability to purify the blood, and thus maintain homeostasis. This disease has reached exponential levels of growth with important economic and social impact. Cardiovascular disease is the main cause of mortality in this population. People with chronic kidney disease commonly exhibit traditional cardiovascular risk factors (hypertension, diabetes mellitus, smoking, dyslipidemia, obesity) and non-traditional risk factors such as inflammation, oxidative stress and secondary hyperparathyroidism. Given these facts, this dissertation aimed to investigate the presence of oxidative stress, inflammation and secondary hyperparathyroidism in patients with chronic kidney disease in the aging process who undergo renal replacement therapy. This is an observational, descriptive, cross-sectional study consisting of 73 patients with chronic kidney disease undergoing renal replacement therapy at Hospital São Vicente de Paulo in Passo Fundo-RS. The subjects included in the study were over 50 years old and had been on renal replacement therapy for more than 6 months. Analyzes of biochemical parameters were performed: creatinine, urea, calcium, phosphorus, intact PTH, 25 dihydroxyvitamin D, alkaline phosphatase, blood count; inflammatory parameters: albumin and ferritin; and oxidative stress parameters: nitric oxide, thiobarbituric acid reactive substances (TBARS) and protein and non-protein SH groups. The results generated by this research are presented in a scientific production entitled ¿Oxidative stress, inflammation and secondary hyperparathyroidism in dialysis patients¿. It was not possible to determine that individuals with secondary hyperparathyroidism exhibited higher levels of oxidative stress and inflammation when compared to those without hyperparathyroidism. The data obtained in this study showed that CKD patients on peritoneal dialysis exhibited higher levels of oxidative stress and lower albumin levels when compared to those on hemodialysis, suggesting a greater cardiovascular risk in this population. Another scientific production was also carried out with the title ¿Relation of advanced glycation end products in hypertension in diabetic patients: a systematic review¿, where it was found that prolonged periods of hyperglycemia increase the formation of AGEs. The AGE-RAGE axis is involved in increasing arterial stiffness, inflammation and endothelial changes, thus increasing the risk of hypertension in diabetic patients. Therefore, AGEs should be considered as cardiometabolic risk factors and are generators of oxidative stress and inflammation.